(untitled) (Research, Society and Development, 2025)
Objective: To critically analyze scientific publications on the use of anti-inflammatory drugs concomitantly with collagen biostimulators and their effects on neocollagenesis, seeking to clarify whether there is interference in the neocollagenesis process and what are the best clinical practices to safely enhance therapeutic results. Methodology: A review was conducted in the PubMed, SciELO, Medline, and LILACS databases, using the keywords "collagen," "anti-inflammatory," "calcium hydroxyapatite," "poly-L-lactic acid," and "skin." Scientific articles in Portuguese, English, and Spanish that addressed the relationship between anti-inflammatory drugs and collagen biostimulators were included. Results and Discussion: The reviewed studies indicate that non-steroidal anti-inflammatory drugs (NSAIDs) can negatively interfere with the initial inflammatory phase, which is essential for the action of biostimulators. This interference can inhibit cell migration, angiogenesis, and tissue remodeling, reducing the formation of new collagen. On the other hand, symptoms such as pain, edema, and post-procedure discomfort justify, in some cases, the clinical use of these drugs, reinforcing the need for a careful and individualized assessment. Conclusion: The literature shows that the routine and indiscriminate use of anti-inflammatory drugs after the application of collagen biostimulators should be avoided, as it can compromise the inflammatory response necessary for neocollagenesis. Understanding the mechanisms of interaction between these substances is fundamental to maximizing clinical results and establishing safe and effective protocols.